Implementing a proprioceptive exercise program in elderly - Garcia, Sérgio Alberto Pires (2015)
With aging, the human body goes through a period of transformation that generate decline of some physical capacities, such as decreased flexibility, agility, coordination, joint mobility and balance, compromising the functional capacity of older people, which is essential for carrying out Activities of Daily Living. The physical exercise is key to improving the functional capacity of the elderly, in particular with proprioceptive exercises, which have been used in recent studies with elderly. The aim of our study is to evaluate the effects of a proprioceptive exercise program on functional capacity in the elderly group. To achieve this objective, we designed a quasi-experimental study with pre- and post-intervention. In all participants were evaluated hand grip strength, finger pinch force, the Tinetti Gait and Balance Test , single leg balance test, evaluation of senior fitness test by the "arm curl test", "sit to stand test" "timed up and go test", "back scratch test" and "chair, sit and reach test " by Rikli & Jones. The program was conducted 2 times a week for 12 weeks. The sample was consisted of 24 elderly, 12 of them in the intervention group (67.25 ± 2.01 years) and the other 12 in control group (68.08 ± 1.73 years). According to the results, the intervention group showed a statistically significant improvement in all evaluations performed after the program. In the control group, there was no significant improvement in functional capacity component evaluated after 12 weeks. Our proprioceptive exercise program proved to be decisive in improving the functional capacity of the elderly. This proprioceptive training program is one of the pioneers in this specific area with great potential for future use.